Characterization of Groundnut (Arachis hypogaea L.) Test Locations Using Representative Testing Environments With Farmer-Preferred Traits - Oteng-Frimpong, Richard; Kassim, Yussif Baba; Puozaa, Doris Kanvenaa; Nboyine, Jerry Asalma; Issah, Abdul-Rashid; Rasheed, Masawudu Abdul; Adjebeng-Danquah, Joseph; Kusi, Francis (Frontiers in Plant Science, 2021)
In this study, the differential rankings of 36 groundnut genotypes under varying environmental conditions was studied at various levels of phenotype. Locations that are generally accepted by the crop- and soil-based research community (consensus locations) to represent the entire Guinea and Sudan Savanna agro-ecological zones in Ghana were characterized, this time using a crop. The characterization was done based on four (4) farmer preferred traits (early and late leaf spot disease ratings, and haulm and pod yields) using three models (i.e., AMMI, GGE and Finlay-Wilkinson regression). These models were used to capture specific levels of phenotype namely, genotype-by-environment interaction (GE), genotype main effect plus genotype-by-environment interaction (G+GE) and environment and genotype main effects plus genotype-by-environment interaction (E+G+GE), respectively. The effect of three (3) major environmental covariables was also determined using factorial regression. Location main effect was found to be highly significant (p<0.001) confirming its importance in cultivar placement. However, unlike genotypes where the best is usually adjudged through statistical ranking, locations are judged against a benchmark, particularly when phenotyping for disease severity. It was also found that the locations represent one complex mega environment justifying the need to test new technologies, including genotypes in all of them before they can be approved for adoption nationally. Again, depending on the phenotypic level considered, genotypic rankings may change causing environmental groupings to change. For instance, all locations clustered to form one group in 2017 for early and late leaf spot diseases and pod yield when GE was considered, but the groupings changed when G+GE was considered for the same traits in the same year. As a result, assessing genotypic performance at the various levels to arrive at a consensus decision is suggested. Genotypes ICGV-IS 141120 and ICGV-IS 13937 were found to be the best performing.